2017
DOI: 10.4209/aaqr.2016.05.0181
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of PM2.5 and Assessing Effects of Emission-Reduction Measures in the Heavy Polluted City of Shijiazhuang, before, during, and after the Ceremonial Parade 2015

Abstract: The measurement of PM 2.5 was conducted from 15 th August to 17 th September, 2015 in Shijiazhuang, China, covering the period of a ceremonial parade. The PM 2.5 concentrations and the major chemical components were analyzed. The concentrations of PM 2.5 was 26.5 µg m -3 during control, which were 57.0% and 51.1% lower compared to before and after control, respectively. The lowest concentrations of elements and water-soluble ions were also found during control with a decreasing tread of 31.1%-44.2%, and 57.1%-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…In recent decades, haze frequently occurred in China because of rapid urbanization and industrialization without an efficient emission control (Huang et al, 2014;Wu et al, 2018;Zhao et al, 2018). Previous studies have demonstrated that both unfavorable diffusion conditions and anthropogenic sources emissions play key roles in the formation of haze pollution (Chen et al, 2017;Wang et al, 2017). Haze events have gained considerable attention because of its significant impact on visibility, air quality, human health, and globle climate change (Kanakidou et al, 2004;Wang et al, 2016;Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, haze frequently occurred in China because of rapid urbanization and industrialization without an efficient emission control (Huang et al, 2014;Wu et al, 2018;Zhao et al, 2018). Previous studies have demonstrated that both unfavorable diffusion conditions and anthropogenic sources emissions play key roles in the formation of haze pollution (Chen et al, 2017;Wang et al, 2017). Haze events have gained considerable attention because of its significant impact on visibility, air quality, human health, and globle climate change (Kanakidou et al, 2004;Wang et al, 2016;Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…He et al (2016) built a statistical model by analyzing the relationship between concentrations of atmospheric pollutants and several factors including potential temperature decline rate, stable energy, Froude number, gradient Richardson number, and so on. Constructing meteorological conditions for air pollution and studying the feasibility of index forecasting are also belong to the conventional statistical forecasting method (Wang et al, 2013;Chen et al, 2015;Yang et al, 2015). The dynamic-statistical forecasting method are based on Chemical Transport Models (CTMs) and linear or nonlinear statistical methods to build a statistical model using the observed or modeled concentrations of pollutants and meteorological elements.…”
Section: Introductionmentioning
confidence: 99%
“…The Yangtze River Delta (YRD) is a special region with a well-developed economy, dense population and high degree of urbanization. Serious heavy haze occurred in China since 2013 (Chen et al, 2017;Wang et al, 2017b;Zhang et al, 2017), especially in North China and the YRD Region (Lang et al, 2017;Wang et al, 2017a). The increase in anthropogenic emissions and disadvantageous meteorological conditions have caused frequent regional air pollution and greatly restricted the accuracy of air quality forecast in this region (Jia et al, 2017;Zhang et al, 2008;Parrish et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…To ensure good air quality during major events, such as the 70th anniversary of the Anti-Japanese War victory and the Asia-Pacific Economic Cooperation, emission controls have been implemented in these regions (the Beijing, Tianjin, Hebei, and Shaanxi provinces). Those measures were implemented successfully, and the pollution levels were low [15,16]. These practices provided opportunities to experiment and explore the atmospheric chemical mechanism in China.…”
Section: Introductionmentioning
confidence: 99%